Produccion y consumo de frijol seco y su contribucion a la oferta de proteina a nivel mundial - Infante, MA; Scobie, Grant M.; Gutiérrez Palacios, Uriel (International Center for Tropical Agriculture, 1974)
There is great concern to develop techniques and policies to remedy the nutritional deficiencies of many of the world`s inhabitants: the Centro Internacional de Agricultura Tropical proposes to emphasize the development of certain crops, one of which is the dry bean Phaseolus vulgaris. This report specifically proposes (1) to review the present status of bean production on a worldwide scale to alleviate protein-rich food shortages; (2) to distinguish levels of bean protein consumption from other sources along broad regional lines; (3) to identify bean product and consumer countries, their protein needs and to quantify their deficiencies, and (4) to identify the state of the international dry bean market in Latin America. Legumes generate 16 percent of the total protein in developing countries, with the dry bean being predominant in Latin America, Africa and the Far East. Dry bean production in L.A. is generally done by small producers, largely in association with other crops, principally, maize. The slow increase in production (2.6 percent/year) during the last 20 years is due to the slight increase in yields. Approx. 64 percent of the bean and